Analytical comparison of "patriotism" in the poetry of early and late Palestinian stability poets based on the poems of "Jabra Ibrahim Jabra" and "Salem Gibran" - Majed morhej. Rebat; Hosein salami; Mohamad javad purabed; Sajjad arabi (Journal of College of Education, 2023)
Patriotism is one of the most important components of any nation that the people of that nation cling to in defense of their identity. This phenomenon has a special and widespread reflection among Palestinian poets; Therefore, influenced by the bitter reality of the occupation of their motherland, they tried to arouse the feeling of patriotism in the souls of the Palestinian people and create a spirit of stability in them, relying on patriotism. For this reason, love for Palestine and one’s motherland, from the very beginning, formed the central theme of the poems of Palestinian resistance poets in such a way that it is rare to find a poet whose poems are devoid of this feature. The following essay tries to analyze the manifestations of patriotism in the poetry of two of the poets of the Palestinian resistance with a descriptive-analytical method. "Jabra Ibrahim Jabra"; To examine the early poets and "Salem Gibran" from the late poets. From the analysis of the two poets’ works, it appears that the sense of patriotism in the poetry of the early Palestinian poets, including "Jabra Ibrahim Jabra", is more than the passage of inner feelings and emotions, while this feature is more prominent in the poetry of later poets, including "Salem Gibran". It gives reality and rationality. Another thing is that "Jabra Ebrahim Jabra", to explain his "patriotism" sometimes resorts to a symbol that raises the artistic mystery of his poetry and in some cases, makes it difficult for the audience to understand the content of his compositions, while the poetry of "Salem Gibran" is clear and short. And it is direct and to a large extent devoid of symbols and symbols. A feature that can be seen in the poetry of the majority of late Palestinian poets.